On two South-West Atlantic Diastylis (Cumacea: Crustacea), D. obliquisulcata n. sp. and D. geocostae, with remarks on this speciose genus - Alberico, Natalia A.; Roccatagliata, Daniel (Zootaxa, 2013)
A new species, Diastylis obliquisulcata from eastern Patagonia, is fully described and illustrated based on specimens col-lected in shallow waters. Diastylis obliquisulcata shares with 14 other species of this genus an opercular maxilliped 3, a short telson and rudimentary exopods on pereopods 3 and 4 in the females. Diastylis obliquisulcata can be easily distin-guished from all these species by the females having an oblique groove or sulcus on each side of the carapace. The taxo-nomic position of this group of species in the genus Diastylis is discussed. The adult male of Diastylis geocostae is described for the first time, the adult female briefly redescribed, and its distribution, up to now known from the type lo-cality only (Cabo Frio, Rio de Janeiro State), is extended to off Rawson, Argentina. Within this species there are reported ontogenetic changes in the carapace ornamentation, in the chaetotaxy of the telson, and in the length ratio between the telson and the uropod peduncl